Ontologies as the base of Semantic web - Boras, Damir (Array, 2005)
World Wide Web is entering its second faze called Semantic web. Today we are talking about new kind of web whose base are ontologies. Broadly speaking, every organized set of subjects can be an ontology, like catalogues and indexes in field of Information retrieval, ER models in Databases, dictionaries and thesauruses in Computational linguistics, object oriented definitions of classes in OO-Programming, etc. Purpose of this paper is to give overview of ontologies, ontological tools and languages, as well as projects dealing with ontologies.